Nitrous Oxide Emissions from Anhydrous Ammonia, Urea, and Polymer‐Coated Urea in Illinois Cornfields. Issue 2 (1st March 2015) - Fernández, Fabián G.; Terry, Richard E.; Coronel, Eric G.
Abstract : The use of alternative N sources relative to conventional ones could mitigate soil‐surface N2 O emissions. Our objective was to evaluate the effect of anhydrous ammonia (AA), urea, and polymer‐coated urea (ESN) on N2 O emissions for continuous corn ( Zea mays L.) production. Corn received 110 kg N ha −1 in 2009 and 180 kg N ha −1 in 2010 and 2011. Soil N2 O fluxes were measured one to three times per week early in the growing season and less frequently later, using vented non–steady state closed chambers and a gas chromatograph. Regardless of N source, N2 O emissions were largest immediately after substantial (>20 mm) rains, dropping to background levels thereafter. Averaged across N sources, 2.85% of the applied N was lost as N2 O. Emission differences for treatments only occurred in 2010, the year with maximum N2 O production. In the 2010 growing season, cumulative emissions (in kg N2 O–N ha −1 ) were lowest for the check (2.21), followed by ESN (9.77), and ESN was lower than urea (14.07) and AA (16.89). Emissions in 2010 based on unit of corn yield produced followed a similar pattern, and N2 O emissions calculated as percent of applied N showed that AA losses were 1.9 times greater than ESN. Across years, relative to AA, ESN reduced N2 O emissions, emissions per unit of corn yield, and emissions per unit of N applied, whereas urea produced intermediate values. The study indicates that, under high N loss potential (wet and warm conditions), ESN could reduce N2 O emissions more that urea and AA.